Role Of The Army In Modern Pakistan - Vladislav Viktorovich Vorobiev (Vestnik MGIMO-Universiteta, 2014)
The article studies the political development of the country in the modern period. Special attention is paid to the position of the army and its role in the Pakistani society. The article explores in detail the processes of gradual distancing of the army from politics and strengthening of civil society institutions. It is the first time in the Pakistani history that the civilian government managed to complete its full five-year constitutional term. Meanwhile, the country has been advancing on the path to democracy even after the elections 2013: a new civilian government has been formed in Pakistan. As compared with the previous phases of the country's development, the status of the army has considerably changed, evolved from "guiding force" to "shadow" guarantee of democratic development. The process has been largely encouraged by popular among officers feeling of tiredness: many of them are not ready to take power into their own hands and committed to their strictly constitutional duties. Despite this recent positive trend, the army continues to enjoy great authority in the society, often brokers political crisis and helps civilian authorities in settling such pressing problems as, for example, fight against extremism. The military will exert influence on government unless civil authorities are able to resist the current challenges and settle the actual problems. The role of "power broker" fully serves the interests of the top army brass.